Seventh Five Year Plan 1985-90 and Annual Plan, 1985-86 Draft Proposals Volume II Sectoral Programmes Government of Meghalaya - Planning Commission (Planning Commission, 1985)
The primary objective of the Sixth Plan was to increase production of foodgrains, Commercial and Horticulture crops so as to improve the economic condition of the rural population of the State and to bring about self sufficiency in foodgrains. Emphasis was, therefore, laid on increasing area under high yielding varieties and improved varieties of seeds facilitating double cropping, systematic plant protection measures against pests and diseases and intensified use of organic manures and chemical fertilizers.
Government of Meghalaya, Planning Department